2016
DOI: 10.1186/s12916-016-0687-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of health-related behavioural factors in accounting for inequalities in coronary heart disease risk by education and area deprivation: prospective study of 1.2 million UK women

Abstract: Background: Some recent research has suggested that health-related behaviours, such as smoking, might explain much of the socio-economic inequalities in coronary heart disease (CHD) risk. In a large prospective study of UK women, we investigated the associations between education and area deprivation and CHD risk and assessed the contributions of smoking, alcohol consumption, physical activity and body mass index (BMI) to these inequalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 49 publications
2
29
0
1
Order By: Relevance
“…More recent studies focusing on the mediation of the association between education and CHD showed that 21–57% of the effect was accounted for behavioral and biological risk factors 10 , 18 , 20 . These and other studies pointed to smoking, BMI, hypertension, PA, lipid profile, and diabetes as mediators of the association between education and CVD incidence 10 , 11 , 13 , 15 , 16 , 20 , 24 , 26 .…”
Section: Discussionmentioning
confidence: 67%
“…More recent studies focusing on the mediation of the association between education and CHD showed that 21–57% of the effect was accounted for behavioral and biological risk factors 10 , 18 , 20 . These and other studies pointed to smoking, BMI, hypertension, PA, lipid profile, and diabetes as mediators of the association between education and CVD incidence 10 , 11 , 13 , 15 , 16 , 20 , 24 , 26 .…”
Section: Discussionmentioning
confidence: 67%
“…Person-years were calculated from the date the baseline questionnaire was completed to first hospital record of any stroke (ICD codes I60–I64), death, emigration, or March 31, 2015 (the latest date when complete information was available), whichever was earliest. Time in study was the underlying time variable, and analyses were stratified by year of birth (1930 or before, 1931 to 1949 in single years, 1950 or later) and of completion of the baseline questionnaire (2000 or before, 2001, 2002, 2003, 2004 or later) and adjusted for region of residence (10 geographical areas in the United Kingdom), socioeconomic status (5 levels of the Townsend index 10 ), educational attainment (tertiary, secondary/technical, no formal qualifications 11 ), and when appropriate for smoking (never, past, current <5, 5–9, 10–14, 15–19, 20–24, ≥25 cigarettes/d), alcohol consumption (none, ≤6, 7–14, ≥15 drinks/wk), body mass index (<25, 25–29.9, ≥30 kg/m 2 ), physical activity (thirds of excess metabolic equivalents), and menopausal hormone therapy (never, past, current). For adjustment variables, missing values were assigned to an unknown category and represented <5% of the data in every variable.…”
Section: Methodsmentioning
confidence: 99%
“…To ensure that analyses compared dementia detection rates in women who were as similar as possible in all other respects, all analyses were routinely stratified by single year of birth (≤1930, 1931…1949, 1950 and later) and by calendar year at recruitment (1996,1997,1998,1999,2000,2001 and later) or, for the diet analyses, at the 3-year resurvey. All analyses were also adjusted for other factors at recruitment: region of residence at baseline (Scotland and 9 areas in England representing NHS Regional Heath Authorities); education (no qualifications, any qualification) 21 ; area deprivation (tertiles based on the Townsend Index 22 ); height (<155, 155-164, 165+ cm); smoking (never, past, current <10, 10-19, 20+ cigarettes per day); alcohol consumption (0, <7, 7-14, 15+ drinks per week); and use of menopausal hormones (never, past, current).…”
Section: Statistical Analysesmentioning
confidence: 99%